A New Concept of Multi Electron-Hole Pair Generation using Dark-Bright Soliton Conversion Control - S. Punthawanunt; C. Teeka; R. Jomtarak; S. Mitatha; J. Ali; P.P. Yupapin (My University, 2011)
In this paper, we have derived and presented a new concept of multi electron-hole pair generation by using dark-bright soliton collision within the modified add/drop filter, which it is known as PANDA ring resonator. By using the dark-bright soliton conversion control, the obtained outputs of the dynamic states can be used to form the multi electron-hole pair, which can be available for communication security application.
Keywords: Electron hole; Advanced Fiber Laser Technologies